THE MYSTERIOUS DISAPPEARANCE OF MH370: MALAYSIAN MUSLIM SPIRITUAL AND RELIGIOUS RESPONSE - Bensaid, Benaouda (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2016)
The disappearance of Malaysian Airlines Flight MH370 has led to a remarkable Muslim spiritual response demonstrating a profound mass religious coping phenomenon, and understandably, an intense sense of spirituality; This includes significant, no less relevant issues, such as religious, preaching responses and theological interpretations, the pilots suicidal scenario, the bomohs, and interfaith rapprochement. This study not only highlights the social implications of the spiritual and religious capital inherent in Malaysian society, i.e., indicating of adaptable religious capital in Malaysian society at large, but also unveils to a large degree the extent to which the Malaysian Muslim religious and spiritual capital can play a potentially positive, and effective role in coping with disasters and calamities, and further identifies a collective religious pattern used for adapting to and managing national and international catastrophes and crisis.